1999
DOI: 10.1002/(sici)1096-8628(19990205)88:1<83::aid-ajmg15>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the serotonin transporter promoter region affects serotonin uptake in human blood platelets

Abstract: The human serotonin transporter (5-HTT), encoded by a single gene on chromosome 17q11.2, is expressed in brain and blood cells. 5-HTT is implicated in mood and anxiety regulation, and is where antidepressant and antianxiety drugs initially act in the brain. A 5-HTT-linked promoter region (5-HTTLPR) insertion/deletion polymorphism with long (l) and short (s) forms affects transporter expression and function. The s variant reduced 5-HTT gene transcription in a reporter gene construct and human lymphoblasts, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
248
4
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(270 citation statements)
references
References 11 publications
16
248
4
2
Order By: Relevance
“…These findings are in accordance with functional effects on higher platelet serotonin uptake mediated by the long allele variants of 5HTTLPR in healthy controls. 229 No difference was found between genotypes for whole-blood serotonin levels in two samples of individuals with AD, 236,245 which parallels the findings in healthy controls.…”
Section: Chromosome 17supporting
confidence: 57%
See 1 more Smart Citation
“…These findings are in accordance with functional effects on higher platelet serotonin uptake mediated by the long allele variants of 5HTTLPR in healthy controls. 229 No difference was found between genotypes for whole-blood serotonin levels in two samples of individuals with AD, 236,245 which parallels the findings in healthy controls.…”
Section: Chromosome 17supporting
confidence: 57%
“…The most common assessed variants are a deletion/ insertion polymorphism in the transcriptional control region of the SLC6A4 gene with functional effects (5HTTLPR) [227][228][229] and a variable number of tandem repeat in intron 2 (STin2). Several studies have found an association of the short alleles of 5HTTLPR with AD, 217,[230][231][232][233] fewer studies of the long alleles.…”
Section: Chromosome 17mentioning
confidence: 99%
“…68,[70][71][72][73] However, the translation of in vitro findings into in vivo functioning does not appear straightforward. Human neuroimaging studies of 5-HTT availability [74][75][76][77][78][79] and post-mortem studies of 5-HTT bindings and rRNA expression [80][81][82] have not detected any consistent effect of 5-HTTLPR. No reliable association was found between 5-HTLPR and the level of serotonin metabolite in the cerebrospinal fluid.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%
“…39,38 Serotonin transporter function has been characterized in platelets using [ 3 H]-serotonin with typical K m values reported in the nano-to micromolar range. 19,40 Lymphocyte SERT 30,41 and DAT 42,43 expression have also recently been described. Serotonin transporters are reported to be expressed in primary B-lymphocytes, 41 T-lymphocytes, 41 and mixed lymphocyte populations.…”
mentioning
confidence: 96%
“…Serotonin transporter regulation and function have been studied using radiometric assay, voltammetry, or fluorescence microscopy in synaptosomes, 16−18 platelets, 19,20 peripheral blood cells (PBCs), 21,22 lymphoblasts, 23−25 brain slices, 1 and the intact brains of experimental animals. [26][27][28]2 Although SERT function can be effectively measured by all of these methods, ambiguity arises when samples containing multiple cell types, such as PBCs, are investigated due to the difficulty in assigning uptake to individual cell types.…”
mentioning
confidence: 99%